2019
DOI: 10.1002/jbm.b.34409
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor genes are overexpressed within the periprosthetic soft‐tissue around percutaneous devices: A pilot study

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that FGF-10, EGF, EGFr, and TGF-α are all diferentially expressed within the GT when compared to the healthy skin (i.e., uninjured/ unmodeled dermal tissue) [36][37][38][39][40]. To better understand the progression of healing around the implants, mRNAs were quantifed using qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FGF-10, EGF, EGFr, and TGF-α are all diferentially expressed within the GT when compared to the healthy skin (i.e., uninjured/ unmodeled dermal tissue) [36][37][38][39][40]. To better understand the progression of healing around the implants, mRNAs were quantifed using qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…This may relate to integrin subunit β4 and its participation in EGF-stimulated chemotaxis [ 246 ] or maintenance of epithelial integrity [ 294 ]. The potential role for EGF in percutaneous device/epithelial integrity is supported by a recent report showing EGF and both up- and down-stream genes were highly upregulated in soft tissue immediately surrounding percutaneous implants placed in the backs of rats [ 295 ]. EGF thus may mediate wound healing response to percutaneous device placement, perhaps by controlling HD disassembly as discussed.…”
Section: Important Biomolecules In Junctional Epithelium Homeostatis ...mentioning
confidence: 99%